Women before the court : Law and patriarchy in the Anglo-American world, 1600-1800 - Moore, Lindsay R. (Book collections on Project MUSE., 2019)
This book offers an innovative, comparative approach to the study of women's legal rights during a formative period of Anglo-American history. It traces how colonists transplanted English legal institutions to America, examines the remarkable depth of women's legal knowledge and shows how the law increasingly undermined patriarchal relationships between parents and children, masters and servants, husbands and wives. The book will be of interest to scholars of Britain and colonial America, and to laypeople interested in how women in the past navigated and negotiated the structures of authority that governed them. It is packed with fascinating stories that women related to the courts in cases ranging from murder and abuse to debt and estate litigation. Ultimately, it makes a remarkable contribution to our understandings of law, power and gender in the early modern world.